Effect of AAC technology with dynamic text on the single-word recognition of adults with intellectual and developmental disabilities. (3rd March 2020) - Holyfield, Christine; Light, Janice; Mcnaughton, David; Caron, Jessica; Drager, Kathryn; Pope, Lauramarie
Abstract: Purpose : Single-word recognition can support participation in life, including engagement in leisure activities, navigation through the community, and vocational opportunities. Given the limited reading skills of many adults with intellectual and developmental disabilities (IDD) and limited speech, the current study evaluated the effects of using an augmentative and alternative communication (AAC) app, featuring dynamic text and speech output embedded in visual scene displays, on the single-word recognition performance of six adults with IDD who demonstrated limited speech. Method : A multiple baseline across participants single-subject design was used. Ten target sight words for each participant were selected on an individual basis, based on participant interest. Intervention consisted solely of interactions between investigators and individual participants using the app. Result : In the absence of any formal instruction and solely through the use of the AAC app interaction, three of the six participants demonstrated increased accuracy in single-word recognition. Conclusion : Results from the study were mixed, but suggest that AAC apps which provide the dynamic display of text in conjunction with voice output can assist some adults with IDD in achieving gains in single-word reading.